2012
DOI: 10.1155/2012/106965
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Celiac Disease in Adult Patients with Typical or Atypical Malabsorption Symptoms in Isfahan, Iran

Abstract: Aim. Atypical presentations of celiac disease (CD) have now been shown to be much more common than classical (typical) form. We evaluated the frequency of CD among adult patients with typical or atypical symptoms of CD. Materials and Methods. Patients referred to two outpatient gastroenterology clinics in Isfahan (IRAN) were categorized into those with typical or atypical symptoms of CD. IgA antitissue transglutaminase antibody was assessed and followed by duodenal biopsy. In patients for whom endoscopy was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(39 reference statements)
0
2
0
2
Order By: Relevance
“…A histologia permanece o gold standard do diagnóstico [1][2][3][4][5][6][7] . Deve ser feita biopsia nos doentes com clínica sugestiva, independentemente da serologia, e nos assintomáticos com anticorpos positivos 5,11 . A melhoria ou eventual resolução clínica, laboratorial e histológica, no decurso da restrição de glúten, confirmam o diagnóstico [1][2][3] .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A histologia permanece o gold standard do diagnóstico [1][2][3][4][5][6][7] . Deve ser feita biopsia nos doentes com clínica sugestiva, independentemente da serologia, e nos assintomáticos com anticorpos positivos 5,11 . A melhoria ou eventual resolução clínica, laboratorial e histológica, no decurso da restrição de glúten, confirmam o diagnóstico [1][2][3] .…”
Section: Discussionunclassified
“…De acordo com diversos estudos, deve rastrear-se DC nos doentes com autoimunidade tiroideia, nomeadamente sob a forma de Tiroidite de Hashimoto e vice-versa [8][9][10][11][12][13][14] . O tratamento da DC diminui a probabilidade de desenvolver outras condições auto-imunes ao longo da vida, as complicações associadas e, no caso de coexistência de hipotiroidismo, melhora o seu controlo, reduzindo as necessidades de levotiroxina 8,10,12 .…”
Section: Discussionunclassified
“…CD manifestations in both children and adults may be difficult to recognize because of the variation in signs and symptoms associated with the condition. Most of the patients attending primary care and gastroenterology clinics present predominantly with gastrointestinal symptoms such as diarrhea, bloating, abdominal pain, and constipation [ 15 , 16 ]. Common symptoms in children under 5 years old include diarrhea, distension, and abdominal pain [ 17 ].…”
Section: Clinical Manifestations Of CD and Subtypesmentioning
confidence: 99%
“…Gluten-sensitive enteropathy, dermatitis herpetiformis (DH), and gluten ataxia (GA) are the main types of gluten-related autoimmune diseases. 1 - 5 Several studies have shown a relationship between hypersensitivity in various organs and gluten intake, even in the absence of histological findings of celiac disease in intestinal biopsy, which is called gluten sensitivity (GS). 6 - 8 The GRDs are heterogeneous diseases, and their pathogenesis mostly includes an immunological attack on the central and peripheral nervous system which is accompanied by neurodegenerative changes.…”
Section: Introductionmentioning
confidence: 99%